Group Counselling from the Cognitive-Behavioral Approach with Underage People Using Addictive Substances from the Casa Jaguar Residential Program of the Institute for Alcoholism and Substance Addiction - González Palacios, Zeanne (2022)
This article aims to systematize the implementation of the cognitive conduct approach in a group called Circle of Peace in an effort to contribute to theoretical and epistemological reflection at Casa Jaguar Center for Underage People. The methodology was based on systematizing experiences. Its central axis was the following question: What factors influence the participation of minors at the Casa Jaguar Residential Program in the intervention process of the Circle of Peace group? The participating minors were 15 males and 10 females from the Casa Jaguar Residential Program and a professional counselor who facilitated the space. The instruments for data collection were logs, monthly plans, emails, and minute books, between 2011 and 2015. In the framework of conclusions, the factor affecting the group process in the initial approaches provided by the professional guidance was the absence of an affective and horizontal relationship with the group. Notwithstanding, in subsequent approaches, based on lessons learned, the counselor focused her interest on establishing an affective bond with the group based on mutual respect. This procedure made it possible to open adequate spaces for the underage participants to express their feelings, thoughts, and needs with self-efficacy.